Elements Of Knowledge In The Leadership Construct Of Special Education Head Teachers In Malaysia - et. al., Suzana Basaruddin, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Leadership and knowledge are two inseparable things. If you want to be a good leader, then you need to fill yourself with enough knowledge. Leaders who are less or ignorant, their leadership will be lame and imperfect. Just as everything requires knowledge, so does leadership. Relevant knowledge such as management, finance and welfare needs to be known by a leader. The situation in schools is also similar, where the headmaster or principal who leads the school, needs to have knowledge related to their leadership. If it is further dedicated to special education, then the leaders involved not only need to have knowledge in school management only, but also need to have knowledge in special education as well as the special needs students themselves. Therefore, this qualitative study was conducted to explore and detail the elements of knowledge on leadership in special education. This study involved an interview session with 11 special education program coordinators representing each district in the state of Johor. The findings of the study show that, knowledge provides a significant indicator of special education leadership. The researcher hopes that the findings of this study can be used as a basic reference for special education leadership to lead special education better.